If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 = -2x + 2(22 + -6x) -12 = -2x + (22 * 2 + -6x * 2) -12 = -2x + (44 + -12x) Reorder the terms: -12 = 44 + -2x + -12x Combine like terms: -2x + -12x = -14x -12 = 44 + -14x Solving -12 = 44 + -14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14x' to each side of the equation. -12 + 14x = 44 + -14x + 14x Combine like terms: -14x + 14x = 0 -12 + 14x = 44 + 0 -12 + 14x = 44 Add '12' to each side of the equation. -12 + 12 + 14x = 44 + 12 Combine like terms: -12 + 12 = 0 0 + 14x = 44 + 12 14x = 44 + 12 Combine like terms: 44 + 12 = 56 14x = 56 Divide each side by '14'. x = 4 Simplifying x = 4
| 3x+14y=203 | | n/2.8-4.9=-7.11 | | x-12x+5=-50 | | 4-3/2 | | 2x+5=9x-16 | | d=c-13p | | 45=16+x | | -4(3x+1)+5=13 | | 16x+7=-73 | | (5p+3)(5p+3)=8 | | 16x=-73 | | -64x=-1280 | | -7x-3(5x+12)=-146 | | -64x=1280 | | 7+x-(3+32/8)=3 | | X/18=X/960 | | 5(y-3)=8(y-6) | | 2/3=4/5m | | 5t-5=7+2a | | 36=1y+5y+12 | | 14u+4u-15u-2u=8 | | 6(6x+6)-5=1+6v | | -21/(x^2+3) | | 8w-2(2+w)=25 | | -7x-6(-2x+10)=-115 | | 5(2+5x)=-28+6x | | 114=10.5x+30 | | y/-15-112=-88 | | -9g+13g=-12 | | 4log^10(3x)=8 | | 2x+12x-2=0 | | -10=b/7 |